Nano-magnetite aggregates in red soil on low magnetic bedrock, their changes during source-sink transfer, and implications for paleoclimate studies - Zhang, Qi; Appel, Erwin; Hu, Shouyun; Pennington, Robert S.; Meyer, Jannik; Neumann, Udo; Burchard, Michael; Allstädt, Frederik J.; Wang, Longsheng; Koutsodendris, Andreas (Journal of geophysical research. Solid earth, 2020)
Soil and lake sediments are important paleoclimate archives often forming a source-sink setting. To better understand magnetic properties in such settings, we studied red soil on low-magnetic bedrock and subrecent sediments of Caohai Lake (CL) in Heqing Basin, China. Red soil is the only important source material for the CL sediments, it is highly magnetic with susceptibilities (χ) of 10−5 m3/kg. The red soil is dominated by pedogenic nano-magnetite ( 10-15 nm) arranged in aggregates of 100 nm, with particle interaction that causes a wide effective grain size distribution in the superparamagnetic (SP) range tailing into stable single-domain behavior. Transmission electron microscopy and broadband frequency χ(f) suggest partial disintegration of the aggregates and increased alteration of the nanoparticles to hematite during transfer of red soil material to CL. This shifts the domain state behavior to smaller effective magnetic grain sizes, resulting in lower χfd% and χ values, and a characteristic change of χ(f). The SP-stable single-domain distribution of the aggregates in red soil could be climate dependent, and the ratio of saturation remanence to χ is a potential bedrock-specific paleoclimate proxy reflecting it. Magnetic properties of the CL sediments are controlled by an assemblage of nanoparticle aggregates and larger-sized bedrock-derived magnetite. The results challenge the validity of the previous paleoclimate interpretation from the 168-m-long Core-HQ (900-30 ka) in Heqing Basin. Disintegration of aggregates could lead to SP behavior with low χfd% without extinction of individual magnetite nanoparticles, and the χfd%-based assumption of SP magnetite dissolution may be wrong.
Gesehen am 13.07.2021